Crotoxin induces cytotoxic effects in human malignant melanoma cells in both native and detoxified forms - Almeida, Tamires Cunha; Giannotti, Karina Cristina; Ribeiro Silva, Lorena Morais; Marques-Porto, Rafael; DeOcesano-Pereira, Carlos; Camargo, Lauren; Chudzinski-Tavassi, Ana Marisa; Reid, Paul; Picolo, Gisele (Frontiers in Pharmacology, 2024)
Introduction: Melanoma, a highly aggressive skin cancer originating in melanocytes, poses a significant threat due to its metastatic potential. While progress has been made in treating melanoma with targeted therapies and immunotherapies, challenges persist. Crotoxin (CTX), the principal toxin in Crotalus durissus terrificus snake venom, exhibits various biological activities, including anti-tumoral effects across multiple cancers. However, its clinical use is limited by toxicity. Thus, exploring alternatives to mitigate adverse effects is crucial. Methods and Results: This study investigates the antitumoral potential of CTX in its native and in a detoxified form, in melanoma cells. Firstly, we demonstrated that detoxified CTX presented reduced phospholipase activity. Both forms proved to be more cytotoxic to SK-MEL-28 and MeWo melanoma cells than non-tumoral cells. In SK-MEL-28 cells, where cytotoxic effects were more pronounced, native and detoxified CTX induced increased necrosis and apoptosis rates. We also confirmed the apoptosis death demonstrated by the activation of caspase-3 and 7, and the formation of apoptotic bodies. Furthermore, both CTX caused cell cycle arrest at the G2/M phase, interfering with melanoma cell proliferation. Cell migration and invasion were also suppressed by both CTX. These results confirm the antitumoral potential of CTX. Discussion: The maintenance of the antiproliferative effects in the detoxified version, with reduced enzymatic activity often liked to harm effects, supports further studies to identify active parts of the molecule responsible for the interesting effects without causing substantial toxic events, contributing to the future use of CTX-derived drugs with safety and efficacy.